تهذيب الشمائل في من خصه الله بأكمل الفضائل - Ibn Hamza | ابن حمزة, Muhammad bin Omar bin Hamza | محمد بن عمر بن حمزة (King Abdulaziz Complex for Endowment Libraries | مجمع الملك عبدالعزيز للمكتبات الوقفية, 2023)
Basmala, Hamdala, and Prayer: Then he says... Muhammad ibn Zain al-Islam... Hamza al-Hanafi... It was stagnating in my mind and salting in my eyes that I compile a summary of the merits of the master of creation... | البسملة والحمدلة والصلاة: أما بعد فيقول... محمد بن زين الإسلام... حمزة الحنفي ... كان يتلجلج في خاطري ويتملح في ناظري أن أجمع نبذة في شمائل سيد الخليقة...